Class Management in the Application of Islamic Education Learning Strategies - Br. Gurning, Novia Limanda; Yanti , Sri (Jurnal Al-Fikrah, 2023)
This study aims to describe classroom management planning, implementation of classroom management, supporting factors and inhibiting factors for classroom management in improving the learning process, and strategies to improve the learning process. This research method is descriptive carried out by preparing and compiling learning tools and instruments. The research results found that the implementation of classroom management in the learning process was carried out by applying several classroom management principles and several approaches. Supporting factors and inhibiting factors for classroom management are the physical, social, emotional conditions and school organization. The strategy used is to condition students to be ready to study in class, learn to concentrate, use appropriate and varied methods, interact educatively and communicatively, and use media according to the material presented.